1984
DOI: 10.1126/science.6328656
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor Receptors in Rat Forebrain: Autoradiographic Identification

Abstract: Corticotropin-releasing factor (CRF) receptors were identified in rat forebrain by autoradiography with an iodine-125-labeled analog of ovine CRF substituted with norleucine and tyrosine at amino acid residues 21 and 32, respectively. High-affinity receptors for CRF were found in discrete areas of rat forebrain, including laminae I and IV of the neocortex, the external layer of the medium eminence, the lateral nucleus of the amygdala, and the striatum. These results are consistent with earlier findings on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(62 citation statements)
references
References 34 publications
3
59
0
Order By: Relevance
“…Post et al, 1981;Charney et al, 1993), such effects might be amplified by stress-induced kindling of various limbic areas, including the amygdala and BNST. The amygdala and BNST show particularly dense concentrations of CRH cell bodies and receptors (Cummings et al, 1983;De Souza et al, 1984;Sawchenko and Swanson, 1985;Sakanaka et al, 1987;Chalmers et al, 1995;Lovenberg et al, 1995), and chronic stress increased CRH mRNA in the CeA and BNST (Mamalaki et al, 1992;Makino et al, 1994aMakino et al, ,b, 1995. Taken together, these data raise the possibility that stress may sensitize CRH systems in limbic structures, such as the amygdala and/or BNST, leading to a persistent increase in CRH transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post et al, 1981;Charney et al, 1993), such effects might be amplified by stress-induced kindling of various limbic areas, including the amygdala and BNST. The amygdala and BNST show particularly dense concentrations of CRH cell bodies and receptors (Cummings et al, 1983;De Souza et al, 1984;Sawchenko and Swanson, 1985;Sakanaka et al, 1987;Chalmers et al, 1995;Lovenberg et al, 1995), and chronic stress increased CRH mRNA in the CeA and BNST (Mamalaki et al, 1992;Makino et al, 1994aMakino et al, ,b, 1995. Taken together, these data raise the possibility that stress may sensitize CRH systems in limbic structures, such as the amygdala and/or BNST, leading to a persistent increase in CRH transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Canteras and Swanson, 1992;Cullinan et al, 1993;Amaral and Witter, 1995). Furthermore, both the ventral hippocampus and the BNST contain a moderate amount of CRH receptors (De Souza et al, 1984;Chalmers et al, 1995;Sawchenko and Swanson, 1985). Therefore, it is conceivable that CRH given intracerebroventricularly primarily binds to the ventral hippocampus and modulates startle amplitude via hippocampal-BNST connections.…”
Section: Abstract: Bed Nucleus Of the Stria Terminalis (Bnst ); Amygmentioning
confidence: 99%
“…Developmental regulation of stress-related [8,20] and other effects of CRH have been demonstrated [1,3]. Autoradiography and radioligand binding studies during early postnatal life in the rat have demonstrated changes in receptor number and regional distribution [5,6,11,12,15]. The two methods have yielded conflicting information regarding CRH receptor distribution in a number of brain regions [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to characterise the CRH receptor began shortly after the discovery of ovine CRH (Vale et al 1981). High-affinity CRH-binding sites were subsequently established in rat and human pituitary glands and brains (Wynn et al 1983, DeSouza et al 1984, as well as in the corticotroph cell line AtT20 (Rosendale et al 1987). Moreover, this receptor was shown to be associated with a cAMP-dependent signal transduction system A model for the CRH peptide and receptor co-evolution in chordates.…”
Section: Corticotrophinmentioning
confidence: 99%